2017
DOI: 10.1007/s10096-017-3102-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for intestinal carriage of CTX-M-type ESBLs in Enterobacteriaceae from a Thai community

Abstract: The incidence of infections caused by antimicrobial-resistant Enterobacteriaceae in Thailand is increasing and human intestinal flora is an important reservoir for these organisms. This study was carried out to determine the intestinal carriage of bla extended spectrum ß-lactamase-positive Enterobacteriaceae (ESBL + E) and AmpC-positive Enterobacteriaceae in a community setting in Northern Thailand, and to identify potential risk factors for carriage. A total of 307 fecal samples were collected from healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
(57 reference statements)
9
24
1
Order By: Relevance
“…The possible impact of home slaughter is supported by a study in Cameroon showing that ESBL‐producing K. pneumoniae isolates disseminate from animals to abattoir workers (Founou et al, ). There were no significant associations between meat consumption and faecal carriage of ESCE/K, which contrast previous studies that have shown regular consumption of meat and consumption of undercooked meat to be risk factors for community carriage of ESBL‐producing Enterobacteriaceae (Hijazi et al, ; Niumsup et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The possible impact of home slaughter is supported by a study in Cameroon showing that ESBL‐producing K. pneumoniae isolates disseminate from animals to abattoir workers (Founou et al, ). There were no significant associations between meat consumption and faecal carriage of ESCE/K, which contrast previous studies that have shown regular consumption of meat and consumption of undercooked meat to be risk factors for community carriage of ESBL‐producing Enterobacteriaceae (Hijazi et al, ; Niumsup et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…The demonstrated community carriage of ESCE/K in humans and livestock in Cambodia (20% in humans and 23% in livestock) is similar to a recent report on ESBL‐producing E. coli colonization in chicken farmers (20%) and chickens (35%) from Vietnam (Nguyen et al, ) but lower than in reports from Thailand (62%) and Vietnam/Laos (41%–70%) (Nakayama et al, ; Niumsup et al, ). The lower detection frequency in our study could be due to the rural habitat of the sampled population and that previous thawing of some samples has led to an underestimation of human carriage.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although we did not test dried meat samples for ESBL-producing E. coli contamination, our finding is consistent with those of other studies ( 8 , 9 ). Women reported having prepared dried poultry at home.…”
Section: The Studysupporting
confidence: 93%